The Fourier Series: A Historical Perspective - Ortiz Fernández, Alejandro (2018)
The ain of this paper is present a vision of an essential field of the modern analysis like it is the Fourier analysis. we focus on some historical aspects and then we explain the analytical arguments that are accessible to understand.We think this subject is not very well know in Peru, our country, especially inthe way we address this subject. By the other hand, this text is about the classical aspects of the Fourier theory.